2021
DOI: 10.1186/s40478-021-01294-4
|View full text |Cite
|
Sign up to set email alerts
|

Impaired SorLA maturation and trafficking as a new mechanism for SORL1 missense variants in Alzheimer disease

Abstract: The SorLA protein, encoded by the SORL1 gene, is a major player in Alzheimer’s disease (AD) pathophysiology. Functional and genetic studies demonstrated that SorLA deficiency results in increased production of Aβ peptides, and thus a higher risk of AD. A large number of SORL1 missense variants have been identified in AD patients, but their functional consequences remain largely undefined. Here, we identified a new pathophysiological mechanism, by which rare SORL1 missense variants identified in AD patients res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 62 publications
3
31
0
2
Order By: Relevance
“…Here, we used stringent criteria to restrict our analysis to a set of variants with homogeneous effect (PTV + Mis3-LoF), in accordance with our simulation study. Indeed, since Mis3 variants were defined solely through bioinformatics prediction tools in case-control studies, we can expect that there is some diversity of the variant effects on the encoded SorLA protein function towards Aβ secretion [ 33 ], so that our estimates may not be directly translated to all Mis3 SORL1 variants. Moreover, the penetrance curves reflect well the penetrance associated with one SORL1 -LoF variant and may not predict what is expected for a carrier of bi-allelic SORL1 -LoF variants.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we used stringent criteria to restrict our analysis to a set of variants with homogeneous effect (PTV + Mis3-LoF), in accordance with our simulation study. Indeed, since Mis3 variants were defined solely through bioinformatics prediction tools in case-control studies, we can expect that there is some diversity of the variant effects on the encoded SorLA protein function towards Aβ secretion [ 33 ], so that our estimates may not be directly translated to all Mis3 SORL1 variants. Moreover, the penetrance curves reflect well the penetrance associated with one SORL1 -LoF variant and may not predict what is expected for a carrier of bi-allelic SORL1 -LoF variants.…”
Section: Discussionmentioning
confidence: 99%
“…The V118M variant detected in our patient localized between two previously characterized mutations S114R and S124R in SORLA protein [ 76 ]. The S124R mutation showed a maturation profile similar to the wild-type protein, and the S114R mutation led to the decreased production of a mature, glycosylated form of the protein, which resulted in inefficient transport to the cell membrane [ 76 ]. It is thus plausible that also V118M variant may affect maturation defects and cellular localization of SORLA since position 118 in the protein is strongly conserved (phyloP100way).…”
Section: Discussionmentioning
confidence: 90%
“…A recent functional study revealed that many SORL1 rare variants resulted in altered maturation and cellular trafficking of the SORLA protein [ 76 ]. The V118M variant detected in our patient localized between two previously characterized mutations S114R and S124R in SORLA protein [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathways include immune system [83], adaptive immune system [84], neutrophil degranulation [85], cytokine signaling in immune system [86] and GPCR ligand binding [87] were responsible for progression of COVID-19 infection. A previous study demonstrated that the expression levels of AHSP (alpha hemoglobin stabilizing protein) [ [105], ATM (ATM serine/threonine kinase) [106], CD28 [107], LRRK2 [108], CCL5 [109], CD33 [110], FCRL3 [111], CCR3 [112], FGL2 [113], GZMA (granzyme A) [114], PICALM (phosphatidylinositol binding clathrin assembly protein) [115], ALOX5 [116], MME (membrane metalloendopeptidase) [117], VIM (vimentin) [118], CD93 [119], GCA (grancalcin) [120], CD226 [121] RASGRP1 [130], TLR2 [131], DOCK2 [132], CSF1R [133], PRKCB (protein kinase C beta) [134], CAMK4 [135], CXCL5 [136], CD36 [137], P2RY12 [138], LILRB2 [139], CD5 [140], SLC25A37 [141], ADIPOR1 [142], PECAM1 [143], RGS10 [144], RGS18 [145], ANK1 [146], RNF182 [147], NPRL3 [148], NINJ2 [149], KCNA3 [150], ABCG2 [151], MS4A6A [152], WDR45 [153], RAB39B [154], SORL1 [155], LRRN3 [156], DPM2 [157], SLC4A10…”
Section: Mirna-hub Gene Regulatory Network Constructionmentioning
confidence: 99%